Students advisee system (SAS) / Bahariah Napiah - Bahariah, Napiah (2003)
Students advisee system(SAS) is a system that will help as a way for interaction among students and with their academic advisor, This system may be very useful for the faculty of computer science and information technology areas. The main objective of SAS project is to create a web based application for interaction between students and academic advisor. In this system students allow to share their problem with their academic advisor directly without any limit. SAS includes 7 important modules and the main modules are Chat Room and Mail modules. Hopefully this system will be the most useful system and may be a very good system for students to share the problems with their academic advisor and this interactions can helps students to improve their archivements in their study and life.